IMPLEMENTASI METODE MUSTAQILI DALAM MENGHAFAL MUFRADAT PADA PEMBELAJARAN DI SD SABBIHISMA 04 PADANG - Fuji Arifzapni; R Mhd Kadri (STKIP Pesisir Selatan, 2026)
Arabic vocabulary (mufradat) learning in elementary schools still faces various challenges, particularly students’ low vocabulary mastery and learning motivation. This condition is also found among fifth-grade students at SD SABBIHISMA 04 Padang. This study aims to explore in depth the implementation of the Mustaqili Method in teaching vocabulary and to identify students’ responses, the obstacles encountered, and its impact on the learning process. This research employs a qualitative approach with an exploratory design. The subjects of the study include fifth-grade students and an Arabic language teacher. Data were collected through observation, interviews, and documentation. The data were analyzed descriptively through qualitative procedures, including data reduction, data display, and conclusion drawing. The results show that the Mustaqili Method enhances student engagement, facilitates vocabulary mastery, and creates a more active, interactive, and enjoyable learning atmosphere. However, several challenges remain, such as limited instructional time and differences in students’ abilities. This study concludes that the Mustaqili Method has significant potential to be further developed as an alternative strategy for teaching Arabic vocabulary in elementary schools to improve learning quality sustainably.